2017
DOI: 10.1189/jlb.3mr0117-026rr
|View full text |Cite
|
Sign up to set email alerts
|

How neutrophils resist shear stress at blood vessel walls: molecular mechanisms, subcellular structures, and cell–cell interactions

Abstract: Neutrophils are the first cells arriving at sites of tissue injury or infection to combat invading pathogens. Successful neutrophil recruitment to sites of inflammation highly depends on specific molecular mechanisms, fine-tuning the received information into signaling pathways and converting them into well-described recruitment steps. This review highlights the impact of vascular flow conditions on neutrophil recruitment and the multitude of mechanisms developed to enable this sophisticated process under wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 101 publications
1
33
0
Order By: Relevance
“…5I). As the basic properties and phenotypical and functional characteristics of dHoxb8 cells were very similar to freshly isolated murine neutrophils (4,37), we concluded that this model represents a useful tool to study neutrophil trafficking.…”
Section: Dhoxb8 Cells Represented a Valid Model For Neutrophil Traffimentioning
confidence: 67%
See 1 more Smart Citation
“…5I). As the basic properties and phenotypical and functional characteristics of dHoxb8 cells were very similar to freshly isolated murine neutrophils (4,37), we concluded that this model represents a useful tool to study neutrophil trafficking.…”
Section: Dhoxb8 Cells Represented a Valid Model For Neutrophil Traffimentioning
confidence: 67%
“…During acute inflammation, neutrophils are the first leukocytes to arrive at the site of injury (1,2). The recruitment of neutrophils from the blood stream into the inflamed tissue follows a consecutive multistep cascade that includes capturing, rolling, firm adhesion, adhesion strengthening, spreading, intraluminal crawling, transmigration, abluminal crawling, and interstitial migration to sites of lesion (3,4).…”
mentioning
confidence: 99%
“…Our finding of enhanced in vitro neutrophil binding parallels the increased adhesion seen in vivo in the setting of our murine model of HIT, with or without endothelial cell injury. We speculate that neutrophil adhesion immediately downstream of growing venular injury may be due to increased turbulent flow around larger thrombi that is known to enhance neutrophil adhesion to the endothelial lining (34). It may also be due to the release of PF4 from activated platelets within the thrombus that results in increased assembly of antigenic complexes on the downstream endothelium, leading to more HIT antibody binding and endothelial activation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PMNs ligate immobilized chemokines presented on inflamed endothelial cells, thereby inducing the high‐affinity conformation of β 2 ‐integrins lymphocyte function‐associated antigen‐1 (LFA‐1) and macrophage‐1 antigen (Mac‐1), which leads to firm adhesion of neutrophils on the inflamed endothelium . Postarrest modifications, including β 2 ‐integrin clustering and anchoring to the cytoskeleton, result in neutrophil spreading, adhesion strengthening and intraluminal crawling . Crawling of neutrophils along the inflamed vessel wall is a critical step for their localization at appropriate sites for extravasation (diapedesis).…”
Section: Neutrophil Recruitment Cascadementioning
confidence: 99%
“…6 Postarrest modifications, including b 2 -integrin clustering and anchoring to the cytoskeleton, result in neutrophil spreading, adhesion strengthening and intraluminal crawling. 7 Crawling of neutrophils along the inflamed vessel wall is a critical step for their localization at appropriate sites for extravasation (diapedesis). Similar to the intravascular adhesion steps, emigration of neutrophils into inflamed tissue also proceeds in a cascade-like fashion including transmigration across the endothelial layer into the subendothelial space, followed by penetration of the vascular basement membrane.…”
mentioning
confidence: 99%